Report of the Sub Group of Metropolitan Transport Team - Planning Commission (Metropolitan Transport Team Planning Commission Government of India, 1973)
The report by the Metropolitan Transport Team under the Fifth Five Year Plan evaluates the status and development needs of metropolitan rail transport in Calcutta, Bombay, Madras, and Delhi. It highlights the rapid population growth and consequent surge in travel demand between 1931 and 1971, with forecasts indicating substantial increases in daily trips by 1983. Existing suburban rail systems face severe congestion due to overcapacity, inadequate rolling stock, and infrastructure constraints. The report recommends the development of grade-separated rapid transit systems integrated with urban planning, electrification of suburban routes, optimization of train services, and significant infrastructure investments totaling Rs. 458.30 crores. A coordinated, city-wide mass transit strategy is emphasized as critical for supporting economic activity, improving commuter experience, and addressing the challenges of urbanization in India’s major metropolitan areas.
Metropolitan Transport Team, Planning Commission July 1973
Metropolitan Transport Team, Planning Commission July 1973
Keywords: Metropolitan Transport; Urban Transit; Rapid Transit Systems; Suburban Rail; Population Growth; Infrastructure Investment; Calcutta; Bombay; Madras; Delhi; Electrification; Mass Transit